Moringa Nastar Increase Prolaktin As Support Of 1000 HPK Action With UNICEF Consept Approach - Isnaeni, Ely; Rahmawati, Erna (Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Background: The percentage of exclusive breastfeeding decreases with increasing age groups of infants. The desire for exclusive breastfeeding is not supported by maximum milk production and the main reason is time constraints due to work so that it is not possible to provide breast milk directly or by way of pumping breast milk. The more nutrients that enter the mother, the more the hormone prolactin, and the more milk production. Moringa contains phytosterol compounds that work to increase and facilitate the production of breast milk (lactagogum effect).Purpose: This research was conducted to analyze the effect of Moringa Moringa to increase prolactin as a supporter of the 1000 HPK movement with the UNICEF concept framework approach.Methods: The research design uses pre-experiment research design with one group pre-post tests design. Data were collected using purposive sampling with a total sample of 10 respondents. Data were analyzed using non-parametric data analysis techniques with the Mann Whitney test with ? = 0.05, to see the effect of Nastar Moringa increasing Prolactin as a Supporter of the 1000 HPK Movement With Increased Unicef Conceptual Framework.Result: The results of the study with the Mann Whitney test showed that the influence of Moringa nastar to increase prolactin levels was pvalue = 0.047. Before given Moringa nastar, the mean was 37.06 and after given Moringa nastar increased to 56.51.Conclusions: it is concluded that there is an influence of Nastar Moringa to increase prolactin as a supporter of the 1000 HPK movement. Based on the results of this study it is recommended that mothers consume Moringa nastar to increase levels of Prolactin